Evaluation of the difference in the onset type between cardiogenic cerebral embolism caused by paroxysmal atrial fibrillation and artery to artery embolism - Suzuki, Keisuke; Takekawa, Hidehiro; Hirata, Koichi; Asakawa, Yohei (Journal of Japanese Congress on Neurological Emergencies, 2013)
Sudden onset of neurological deterioration suggests cardiogenic cerebral embolism (CE) rather than other types of ischemic stroke. Recent advances in diagnostic methods have improved the accuracy of the differentiation betweenartery to artery embolism and CE caused by paroxysmal atrial fibrillation (CEP). The aim of this study is to evaluate whether analysis on the type of onset can contribute to differentiation between CEP and artery to artery embolism due to carotid artery stenosis (AES). The subjects were 15 consecutive patients with AES and 30 consecutive patients with CEP. CEP patients were older and had a lower diastolic blood pressure on the initial examination than AES patients (P<0.05); however, there were no differences in the other background factors. No significant difference in the onset type was observed between the two groups. Acute onset progressive type was the major type of onset in both AES and CEP groups. Our results indicate difficulty in differentiating between AES and CEP based on the difference in characteristics of stroke onset, background factors, and initial examination. We should be cautious about the clinical judgment of stroke subtype according to the onset type of stroke.